A case of autoimmune induced necrotizing myopathy - Udani, Jaison; Alekseyev, Kirill; Lakdawala, Malcolm; Patel, Jitendra; Ross, Marc (International Journal of Advances in Medicine, 2016)
A 31-year-old female, with no previous past medical history, presented to the emergency department (ED) two weeks after falling while moving furniture complaining of increasing weakness and swelling. Initially, she had minor ankle pain after falling but this progressed to bilateral ankle pain and eventually bilateral shoulder pain. Creatine Kinase (CK) levels were drawn and results showed a level of 30,186. She was diagnosed with rhabdomyolysis and aggressive IV hydration was initiated. After 3 weeks, her CK levels did not decrease below 15,000. A muscle biopsy was performed and revealed a necrotizing myopathy with high probability of autoimmune etiology.